Pediatric type I tympanoplasty: A study of factors affecting outcome - Valente, Pedro (2020)
Aim: Assess the results of type I tympanoplasty in pediatric patients and identify possible prognostic factors that may influence the success of this intervention.  Study Design: Retrospective.  Material and Methods: Review of pediatric patients submitted to type I tympanoplasty, according to Portmann’s classification, in Centro Hospitalar Vila Nova Gaia/Espinho, between 2001 and 2019.  Results: A total of 146 surgeries were performed in this period. The anatomical success rate was 77.5% and audiometric success rate was 82.8%, with an improvement in the air-bone gap in the postoperative period (24.4 vs 13.4dB; p<0.001). Perforations associated with recurrent acute otitis media and surgeries performed during summer months presented greater anatomical success (p=0.005 e p=0.024; respectively); as opposed to closure of subtotal perforations that showed inferior audiometric success (p=0.021).  Conclusions: Type I tympanoplasty is an effective procedure for closing tympanic perforations and improving hearing loss in pediatric patients.